2011
DOI: 10.1002/app.34418
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing and fastness properties of polyamide fabrics using some acid‐based monoazo disperse dyes

Abstract: A series of monoazo disperse dyes derived from naphthalimide containing butyric acid has been applied on polyamide fabrics. The build up and dyeing properties of these dyes such as leveling property, wash, light, perspiration for alkaline and acidic conditions, and rubbing fastnesses on polyamide fabrics have been investigated. The results showed that the applied dyes are capable of producing red to bluish red hues on polyamide fabrics. Because of the presence of both carboxylic acid and hydroxyl groups on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Nylon yarns were first scoured with 0.5 % nonionic detergent at 60°C for 30 min (Sadeghi-Kiakhani et al 2011). Wool yarns were treated with a solution containing 2 g/L nonionic detergent and 1 g/L sodium carbonate at 70°C for 30 min (Farizadeh et al 2010).…”
Section: Scouring Methodsmentioning
confidence: 99%
“…Nylon yarns were first scoured with 0.5 % nonionic detergent at 60°C for 30 min (Sadeghi-Kiakhani et al 2011). Wool yarns were treated with a solution containing 2 g/L nonionic detergent and 1 g/L sodium carbonate at 70°C for 30 min (Farizadeh et al 2010).…”
Section: Scouring Methodsmentioning
confidence: 99%
“…However, researchers have noted that there are no simple relationships between the absorption properties of disperse dyes in solution and the colorimetric data of dyed fabrics [1].…”
Section: Nylon Dyeing Propertiesmentioning
confidence: 99%
“…The FTIR spectrum of these compounds revealed differences 182 compare with together. The most important differences are given 183 in detail in our previous works [22,23], and readers can see data of 184 the characterization of CS-PPI which are given in the supporting 185 information. FTIR, 1 H NMR and 13 C NMR analyses confirmed that 186 the interaction between chitosan and Ea has been accomplished 187 chemically according to Michael's addition reaction.…”
mentioning
confidence: 98%
“…After three days, the mixture was evaporated to 96 dryness, dispersed in NaOH solution at room temperature for 2 h, 97 dialyzed, and lyophilized to give CS-PPI. The summarized 98 preparation of CS-PPI is illustrated in Scheme 1 and was described 99 in detail in our previous work [22]. thus improving the quality of the prediction.…”
mentioning
confidence: 99%
See 1 more Smart Citation